2007
DOI: 10.1007/s10661-006-9344-0
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of the Impact of Land-Use Changes on Ecosystem Services: A Case Study in Pingbian County, China

Abstract: Pingbian Miao Autonomous County is one of the poorest rural areas in China. Land-use changes, mainly driven by agricultural expansion and deforestation, may significantly impact ecosystem services and functions, but such effects are difficult to quantify. In the present study, Landsat image data were combined with the published coefficients about the world and China ecosystem to quantify land-use and ecosystem service changes in the mountainous area. A sensitivity analysis was employed to determine the effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
91
1
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 185 publications
(100 citation statements)
references
References 23 publications
5
91
1
3
Order By: Relevance
“…The effect of land use on ecological vulnerability Land use and land cover are the main determinants of the structure, function, and dynamics of most landscapes throughout the world (Wu and Hobbs 2002;Li et al 2007). Changes in land use, particularly in ecologically important land use categories, may significantly affect ecosystem processes and services.…”
Section: Analysis Of Vulnerability Evaluation Resultsmentioning
confidence: 99%
“…The effect of land use on ecological vulnerability Land use and land cover are the main determinants of the structure, function, and dynamics of most landscapes throughout the world (Wu and Hobbs 2002;Li et al 2007). Changes in land use, particularly in ecologically important land use categories, may significantly affect ecosystem processes and services.…”
Section: Analysis Of Vulnerability Evaluation Resultsmentioning
confidence: 99%
“…Su et al (2012b) found that considerable urban expansion led to a loss of 8.5 billion RMB yuan ecosystem-service values per year on average between 1994 and 2003 in the Hang-Jia-Hu ecoregion of China. Furthermore, the number of studies on this topic on local scales has grown rapidly (Hu et al, 2008;Li et al, 2007;Zhao et al, 2004). Based on the aforementioned literature, we found that basic benefit transfer (assuming a constant unit value per hectare of a given ecosystem type multiplied by the area of each type to arrive at an aggregate total (Costanza et al, 2014)) is still a simple and easy method of determining ESVs on global and national scales.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to issues with available data, determining unit values of ecosystem services remains a challenge. Although relevant studies have focused on the dynamic changes in ESVs in China on regional, city or county scales Hu et al, 2008;Li et al, 2007Li et al, , 2010aWan et al, 2015;Zhao et al, 2004), national investigations are still lacking. However, aggregates of these data to form a national picture can be used to revise national income figures (Costanza et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Human beings and other organisms benefit directly and indirectly in many ways from their ecosystems, such as through the provision of food and resources, storing carbon, air purification, biodiversity protection, pharmaceuticals, and the regulation of local climates [1,2]. As an important part of the biosphere, ecosystem services maintain the environment, and understanding the multiple benefits provided by the ecosystems is becoming increasingly important [3].…”
Section: Introductionmentioning
confidence: 99%